Investigation on the Properties of Phenolic-Resin-Based Functional Gradient Thermal Protection Composite Materials - Jiangman Li; Weixiong Chen; Jianlong Chang (Aerospace)
Crosslinked phenolic resin was prepared using hexamethylenetetramine (HMTA) as a crosslinking agent in hydrochloric acid solution. The ablation-heat-resistant material was prepared by a pressure-assisted RTM (resin transfer molding) process with reinforcing material (quartz fibre 2.5D needle-punched fabric/satin fibre cloth/fibre mesh tire) and matrix (crosslinked phenolic resin). The thermal stability of the cured product was studied by a thermogravimetric analyser (TG and DTG). The mechanical properties, heat resistance, and ablation properties of the composites were tested. The ablation morphology, element analysis, and phase structure of the composites were analysed by scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), and X-ray diffraction (XRD), respectively. The results show that the phenolic resin has a lower initial viscosity and a longer pot life at 80 °C, and a higher carbon residue rate (70.18%). The tensile strength of the composites is close to 40 MPa, the tensile modulus is higher than 1.35 GPa, the compression modulus is higher than 10 MPa, and the elongation at break is higher than 1.55%. SiO2, SiC, and ZrO2 ceramic phases were formed after ablation, which effectively improved the ablation performance of the composites.